Implementation of The Eco-Print Technique In Improving The Early Childhood Naturalist Intelligence - Kasih, Delina; Utami, Fitria Budi; Rahayu, Wening (Universitas Sebelas Maret, 2023)
This study focuses on improving childhood naturalist intelligence in understanding living organisms, particularly plants, and fostering creative activities. The study utilizes eco-print technique activities to facilitate this improvement. It also assesses the effectiveness of the eco-print technique in enhancing naturalist intelligence among children. It explores eco-printing techniques to boost the naturalist intelligence of 4-6-year-old children at SPS Taam Al-Hidayah, Bandung. The study involves 15 children aged 4-6 years as participants. Following the Kemmis and McTaggart model, the study employed the Classroom Action Research method, involving pre-cycle, cycle 1, and cycle 2 phases, each with planning, action, observation, and reflection stages. The qualitative data is complemented by percentage values from each cycle, reflecting the progress in children's naturalist intelligence enhancement using the eco-print technique. The results include presentations of five indicators: pre-cycle, cycle I, and the final action in cycle II, showing values of 40.33%, 60.33%, and 84.33%, respectively